‘As Though It Were A Sacred Relic’: The Troubled Holocaust Poetry of Julian Tuwim - Myer Siemiatycki (Czytanie Literatury)
The Polish-Jewish poet Julian Tuwim (1894–1953) was among the most widely read – and denounced! – writers of interwar Poland. Described as ‘a virtuoso of language’ in his beloved Polish mother tongue, Tuwim’s literary range was remarkable and varied. Most introspectively, his poetry expressed a simultaneous embrace and ambivalence, towards the dual identities he fiercely proclaimed: both Polish and Jewish. His poetry combined, stretched and challenged identities in unprecedented ways. This writing earned Tuwim a wide audience, along with many critics. Living in exile during the Second World War, Tuwim was among the first major European literary figures to write Holocaust poetry as genocide was being perpetrated. His searing Holocaust poems convey a longing for Poland, for a better Poland, and a solidarity of suffering with his brethren Jews. To the end, Julian Tuwim was a powerful, troubled Polish-Jewish literary voice. He was ever hunting for the words that could change his world and ours.